Words Speak Louder without Actions - LEVIT, DORON (Journal of Finance, 2020)
ABSTRACT Information and control rights are central aspects of leadership, management, and corporate governance. This paper studies a principal‐agent model that features both communication and intervention as alternative means to exert influence. The main result shows that a principal's power to intervene in an agent's decision limits the ability of the principal to effectively communicate her private information. The perverse effect of intervention on communication can harm the principal, especially when the cost of intervention is low or the underlying agency problem is severe. These novel results are applied to managerial leadership, corporate boards, private equity, and shareholder activism.